Еволюція удосконалення машин постійного струму та перспективи їх подальшого розвитку - Лущик, В.Д.; Варванський, А.Ю. (Електротехніка і електромеханіка, 2011)
Operating principle for DC machines with a non-salient-pole stator and an asymmetrical compensation winding is explained. Advantages of these machines are grounded relative to power indexes and specific consumption of copper wire as compared with all other types of electric machines. Advantages of DC motors application in transport machines are underlined.